Adsorption isotherm, kinetics and response surface methodology optimization of cadmium (Cd) removal from aqueous solution by chitosan biopolymers from cephalopod waste. (1st June 2023) - Kavisri, M.; Abraham, Marykutty; Namasivayam, S.Karthik Raja; Aravindkumar, J.; Balaji, D.; Sathishkumar, Ramamoorthy; Sigamani, Sivaraj; Srinivasan, Ramachandran; Moovendhan, Meivelu
Abstract: The present investigation was aimed to explore the cadmium removal efficiency, mechanism and characterization of Chitosan biopolymers from cephalopods waste. The extracted chitosan has showed good yield of 32% and with high minerals, ash and moisture content. In the Fourier-transform infrared spectroscopy (FT-IR) analysis multiple active functional groups of Amine, Amine, Hydroxyl were found between 612 and 3424 cm −1 and the sugar signals such as N-acetyl glucosamine (GlcNAc) and H-1 [GlcN (H-1D), GlcNAc (H-1A)] were identified in Chitosan by 1 H Nuclear Magnetic Resonance (NMR). The Crystalline, rough surface, micropores characters were observed in Chitosan surface by Scanning Electron Microscope (SEM) analysis and the pores played a key role in adsorption process. The Cd ions removal was performed by batch experiment and the results were revealed that the pH, temperature, time and dosage highly influenced the process and the optimum condition was discovered through RSM for pH 7, temperature 42.5 °C, time 220 min and dosage of sorbent 1 g/L respectively. The kinetics models of the Cd removal were carried out and the results revealed that the Pseudo-second order is more suitable and fit for removal than Pseudo-first order model. Chitosan surface characters and functional groups played a big role in adsorption process and Chitosan can be alternative eco-friendly, low cost and highly efficient sorbent for heavy metal removal in effluent treatment plants. Graphical abstract: Image 1 Highlights : Chitosan have more active functional groups and highly involved in Cd removal. Chitosan have suitable surface morphology for Cd removal. Cadmium removal of chitosan was studied through batch experiment. PH, Temperature, time factors are highly influence the Cd removal reaction. Cadmium removal was optimized by RSM and the reaction Kinetics was studied.